Determining the alignment of assessment items with curriculum goals through document analysis by addressing identified item flaws - Humaira Fayyaz Khan; Shazia Qayyum; Huma Beenish; Rehan Ahmed Khan; Samina Iltaf; Lubna Rani Faysal (BMC Medical Education)
Abstract Background Assessment shapes educational activities and curriculum mapping, influences learning outcomes, and motivates students. In medical education, aligning assessment items with curricular goals ensures that learning outcomes are accurately measured. Our study aimed to evaluate the alignment of multiple-choice questions (MCQs) with curriculum objectives, identify any flaws in these items, and propose enhancements to improve assessment quality. Methodology A quantitative descriptive study was conducted at Islamic International Medical College, Riphah University, in 2023. Pre-hoc reports from mid-stake assessments across five academic years were analyzed, covering both preclinical and clinical years. A total of 2,400 multiple-choice questions (MCQs) were reviewed for the mid-stake exams against the institutional checklist in which flaws were categorized into three types: test wiseness, irrelevant difficulty, and miscellaneous flaws. Results The analysis revealed a significant misalignment between assessment items and curriculum objectives. Of the 2,400 MCQs reviewed across all five years, 561 flaws were identified: 125 test wiseness flaws, 198 irrelevant difficulty flaws, and and 238 miscellaneous flaws. The latter category was recognized as “alignment flaws” which was not previously documented.The documentation and rectification of these flaws, which included issues such as misaligned learning objectives, incorrect assessment strategies, and disconnects between scenarios and lead-ins, led to their inclusion in the institutional checklist, facilitating ongoing improvements in assessment quality. Conclusions Our study revealed significant gaps in the alignment of multiple-choice questions (MCQs) with curriculum objectives, emphasizing the need for a systematic approach to address these flaws. Document analysis identified misalignments between content objectives, cognitive processes, and assessment strategies, which compromise the quality of evaluations and can hinder the development of critical thinking and problem-solving skills. To address these issues, we propose integrating identified flaws into institutional guidelines and implementing an updated checklist for pre-hoc evaluation of assessment items, with a focus on curriculum alignment and cognitive levels.